Barriers Against Implementing Blunt Abdominal Trauma Guidelines in a Hospital: A Qualitative Study - Rouhollah Zaboli; Shahram Tofighi; Ali Aghighi; Seyyed Javad Hosaini Shokouh; Nader Naraghi; Hassan Goodarzi (Electronic Physician, 2016)
Introduction: Clinical practice guidelines are structured recommendations that help physicians and patients to make proper decisions when dealing with a specific clinical condition. Because blunt abdominal trauma causes a various range of mild, single-system, and multisystem injuries, early detection will help to reduce mortality and resulting disability. Emergency treatment should be initiated based on CPGs. This study aimed to determine the variables affecting implementing blunt abdominal trauma CPGs in an Iranian hospital. Methods: This study was conducted as a qualitative and phenomenology study in the Family Hospital in Tehran (Iran) in 2015. The research population included eight experts and key people in the area of blunt abdominal trauma clinical practice guidelines. Sampling was based on purposive and nonrandom methods. A semistructured interview was done for the data collection. A framework method was applied for the data analysis by using Atlas.ti software. Results: After framework analyzing and various reviewing and deleting and combining the codes from 251 codes obtained, 15 families and five super families were extracted, including technical knowledge barriers, economical barriers, barriers related to deployment and monitoring, political will barriers, and managing barriers. Conclusion: Structural reform is needed for eliminating the defects available in the healthcare system. As with most of the codes, subconcepts and concepts are classified into the field of human resources; it seems that the education and knowledge will be more important than other resources such as capital and equipment